Differences in Body Water Turnover Rate Between Naja kaouthia Lesson, 1831 and Malayopython reticulatus (Schneider, 1801) Snakes - CHAIYABUTR, NARONGSAK; CHANHOME, LAWAN; VASARUCHAPONG, TAKSA; LAOUNGBUA, PANITHI; PUEMPUNPANICH, SUNUNTA; TAWAN, TANAPONG (Tropical Natural History, 2022)
Total body water and the water turnover were studied in Naja kaouthia Lesson, 1831 and Malayopython reticulatus (Schneider, 1801) snakes by tritiated water dilution techniques. Both snakes species were injected intramuscularly with an aqueous solution carrier-free tritiated water (3H2O) at a single dose of 10 mCi/kg body mass. The equilibration time was determined by taking blood samples for 8 days after the injection. The results show that the absolute values of the rate of water turnover (WTO), water space (TOH) and total body water (TBW) of M. reticulatus were significantly higher than those of N. kaouthia. The relative values of WTO per fat-free, body mass of N. kaouthia were significantly higher than those M. reticulatus, while the biological half-life of tritiated water of N. kaouthia was significantly shorter than those of M. reticulatus. The relative values of both TOH and TBW (% body mass) showed no significant differences between two species. Hematocrit and plasma concentrations of protein, specific gravity, total solid, K+ and Cl- were similar in both snake species, while plasma concentration of Na+ and plasma osmolality were significantly higher in N. kaouthia than M. reticulatus. These results suggest that a lower WTO as a percentage of body mass and a higher biological half-life of 3H2O of M. reticulatus in comparison with N. kaouthia could be attributed to relatively higher efficiency in the water retention mechanism, which M. reticulatus could be a well adaptation to the tropical environment.